UNESCO’s Bioethics activities - ten Have, Hank (Морфологія / Morphologia / Morfologìâ, 2010)
The fundamental significance of the "Universal Declaration on Bioethics and Human Rights of UNESCO" for the formation of bioethics as a global field of knowledge and one of the priorities of this international organization is substantiated. The main directions of UNESCO’s activities in the field of bioethics development are determined. This is a description of the UNESCO Global Ethics Observatory project.